Sabotage surrender - Keene, Carolyn (Keene, Carolyn. Nancy Drew, girl detective, 2011)
When a cash box is stolen from a visiting carnival, Nancy discovers the saboteur is specifically targeting the Mahoney Scholarship Award ceremony, and each candidate for the award is a suspect.